HPV vaccine: is it recommended by the pediatricians of the different health service providers in Montevideo? (Archives of Pediatrics of Uruguay, 2021)
Introduction: the human papillomavirus (HPV) infection is the most frequent sexually transmitted disease globally, associated with pre malignant lesions and uterine cervical cancer. It is the third most frequent type of cancer in Uruguay and the fourth cause of death in women with cancer. There are safe and effective HPV vaccines. In 2013, Uruguay started administering the quadrivalent vaccine (serotypes 16, 18, 11 and 6), for free to all 11-year-old adolescent girls, and in 2019 to all adolescent boys of the same age. The HPV vaccine coverage is still low.Objective: to learn about the position of some pediatricians from Montevideo, Uruguay, regarding the HPV vaccine.Methodology: cross-sectional observational descriptive study, carried out through anonymous, self-administered surveys to some pediatricians from different health providers: Casmu, Armed Forces Hospital, British Hospital and Casa de Galicia, from August to September 2018.Results: total: 67 surveyed pediatricians, 66 recommend the vaccine, 58 believe that they have all the necessary information about the vaccine, 64 understand the indications and contraindications, 63 would like to have official information from the Ministry of Public Health, 63 think that patients do not have adequate information about the vaccine, 21 consider they need between 15 and 30 minutes to give information to patients about the vaccine and 65 think they can influence the parents’ opinions regarding the use of the vaccine.Conclusions: the surveyed pediatricians recommend the HPV vaccine. We need to continue to research the issues of trust in doctors and the need for additional information, as well as other aspects, because they are a negative influence when adolescents and their tutors need to make decisions regarding the use of the vaccine, which results into low adherence.
Keywords: Papillomaviridae; Vaccines; Vaccination coverage; Surveys and questionnaires; Pediatricians